The Effect of PENEMIA (Prevention of Anemia) Video-Based Education on Anemic Pregnant Women on Changes in Knowledge and Attitudes - Hesti Anggraini; Rieska Indah Mulyani; Astri Ayu Novaria; Dini Indo Virawati (Media Publikasi Cendekia Indonesia, 2024)
Pregnant women are a group that is very vulnerable to nutritional problems including anemia. around 41.8% of pregnant women are anemic worldwide. Lack of knowledge and attitudes are the main causes of anemia. This study aims to determine the effect of PENEMIA (Prevention of Anemia) video-based education for anemic pregnant women on changes in knowledge and attitudes at the Harapan Baru Community Health Center, Samarinda City. The research is a quasi-experimental design with one group pre-test post-test design carried out in May - June 2023 in the working area of the Harapan Baru Health Center, Samarinda City, East Kalimantan, Indonesia. A total of 36 anemic pregnant women were involved as respondents by determining inclusion and exclusion criteria. The data was then collected and analyzed using the Wilcoxon test. Our findings show that the difference in the level of knowledge of pregnant women before and after being given PENEMIA education obtained a p-value of 0.000. This means that there is an influence of PENEMIA education on pregnant women's knowledge. The attitudes show differences in the attitudes of pregnant women before and after being given education with a p-value of 0.000, which means there is an influence of nutritional education on the attitudes of pregnant women. PENEMIA educational videos are very effective in increasing the knowledge and attitudes of pregnant women. It is hoped that this education will continue in society